Telomere Shortening, Inflammatory Cytokines, and Anti-Cytomegalovirus Antibody Follow Distinct Age-Associated Trajectories in Humans - Lustig, Ana; Liu, Hans B.; Metter, E. Jeffrey; An, Yang; Swaby, Melissa A.; Elango, Palchamy; Ferrucci, Luigi; Hodes, Richard J.; Weng, Nan-ping (Frontiers in Immunology, 2017)
A number of biological parameters have been cited as hallmarks of immune aging. However, it is not clear whether these multiple biological changes are the result of common underlying aging processes and follow correlated trajectories, or whether the patterns of change for multiple parameters vary across individuals and reflect heterogeneity in the aging process. Here, we have studied parameters of immune system aging through longitudinal analysis of telomere length, inflammatory cytokines, and antibody titer to CMV in 465 subjects ranging in age from 21 to 88 at the first visit, with an average of 13 years (7-19 years) follow-up. We observed a highly variable rate of change in telomere length of PBMCs with a relatively slow average rate of telomere shortening (-16 bp/year). Similarly, there were significant increases with age in vivo in three inflammatory-related cytokines (IFN-, IL-6 and IL-10) and in anti-CMV IgG titer, which varied widely across individuals as well. We further observed positive correlative changes among different inflammatory cytokines. However, we did not find significant correlations among the rate of changes in telomere length, inflammatory cytokines, and anti-CMV IgG titers. Our findings thus reveal that age-related trajectories of telomere attrition, elevated circulating inflammatory cytokines, and anti-CMV IgG are independent, and that aging individuals do not show a uniform pattern of change in these variables. Immune aging processes are complex and vary across individuals, and the use of multiple biomarkers is essential to evaluation of biological aging of the immune system.